2016
DOI: 10.1371/journal.pone.0149666
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Grapevine Leafroll Disease on Fruit Yield and Grape and Wine Chemistry in a Wine Grape (Vitis vinifera L.) Cultivar

Abstract: Grapevine leafroll disease (GLD) is an economically important virus disease affecting wine grapes (Vitis vinifera L.), but little is known about its effect on wine chemistry and sensory composition of wines. In this study, impacts of GLD on fruit yield, berry quality and wine chemistry and sensory features were investigated in a red wine grape cultivar planted in a commercial vineyard. Own-rooted Merlot vines showing GLD symptoms and tested positive for Grapevine leafroll-associated virus 3 and adjacent non-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 38 publications
(32 reference statements)
3
53
0
Order By: Relevance
“…Its associated agents are Grapevine leafroll associated viruses (GLRaVs) belonging to the family Closteroviridae. Of all the GLRaVs, GLRaV-2 and -3 are the most widely spread (Alabi et al, 2016;Almeida et al, 2013;Atallah et al, 2012;Maree et al, 2013;Martelli et al, 2012;Naidu et al, 2015Naidu et al, , 2014. Symptoms vary depending on the viral strain or complex of viruses causing the infection, and are mild in V. labrusca, but severe in V. vinifera (Basso et al, 2014).…”
Section: Grapevine Leafroll Diseasementioning
confidence: 99%
“…Its associated agents are Grapevine leafroll associated viruses (GLRaVs) belonging to the family Closteroviridae. Of all the GLRaVs, GLRaV-2 and -3 are the most widely spread (Alabi et al, 2016;Almeida et al, 2013;Atallah et al, 2012;Maree et al, 2013;Martelli et al, 2012;Naidu et al, 2015Naidu et al, , 2014. Symptoms vary depending on the viral strain or complex of viruses causing the infection, and are mild in V. labrusca, but severe in V. vinifera (Basso et al, 2014).…”
Section: Grapevine Leafroll Diseasementioning
confidence: 99%
“…Using a standard protocol [28], Settesoli winery provided a separate vini cation of the grapes coming from the two soils (about 7,000 kg of grapes per vini cation). The tasting analysis was carried out in Settesoli using the internal trained panel test made up of 13 oenologists (8 males, 5 females).…”
Section: Wines Pro Lesmentioning
confidence: 99%
“…For the wine attributes, the relative differences between wines were analysed and con rmed submitting the judgements to statistical analysis using the ANOVA method according to Alabi et al [28].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Regarding phenols, for most V. vinifera cultivars the phenolic composition of mesocarp tissue is dominated by hydroxycinnamic acids, and therefore this is the most abundant class of phenolic compounds in white wines. Biotic factors such as disease caused by viruses or other pathogens may influence grape ripening development, altering the normal accumulation of sugars, acids, phenolic and aroma compounds . Grape composition at harvest affects wine quality directly since it will influence sensorial parameters such as ethanol content, pH, aroma, taste, and mouthfeel in the wine …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a multi‐seasonal study was conducted to evaluate the impact of grapevine leafroll disease (GLD) on own‐rooted V. vinifera L. Merlot. It showed that the impact of GLD on grape and wine composition and quality was dependent on the season . Another study showed that temperature influenced symptom severity and plant defense against infection of cassava mosaic disease caused by begomoviruses, which belong to the geminivirus family (the same family as GRBV) on cassava ( Manihot esculenta ) …”
Section: Introductionmentioning
confidence: 99%